Đo lường mức độ lan toả không gian trong doanh thu du lịch giữa các tỉnh của Việt Nam - Hoàng Thị Phương , Thảo (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines spatial spillover effects in tourism revenue across Vietnam’s 63 provinces and investigates the influence of institutional factors, including public administration quality, human resources, and local leadership on tourism development. Using 2024 data from the General Statistics Office and the Provincial Competitiveness Index (PCI), a spatial regression model was applied. The results reveal that skilled human resources are the only factor with a significant positive effect on tourism revenue, while transparency, business support policies, and fair competition show no significant impact. The highly significant spatial coefficient (lambda) confirms strong spillover effects in tourism revenue across provinces. The study contributes to spatial and institutional economic theory and offers practical insights for enhancing human resource quality and regional linkages in sustainable tourism planning.